Komunikasi Fatis Dakwah Caknunquotes dalam Media Sosial Instagram - Armaza-Faraba, Karina Sofiananda; Sumarlam, Sumarlam; Purnanto, Dwi (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
This article discusses the form and function of pro-selytizing phatic communication on the Instagram account vi-deo @caknunquotes. By using descriptive qualitative methods through the techniques of listening and note taking, the study found that most of the categories in da’wa on the Instagram video @caknunquotes carried a lot of regional elements or re-gional dialects in the form of particle fat, fatic words, and fatic phrases. With regard to phatic communication function, it expresses courtesy to the congregation, convinces the congre-gation, confirms the contents of the da'wah, asks for approval, greetings to familiarize themselves, as a form of proof of the intent or contents of the preaching, Javanese expression, as emphasis on the sentence sentence, and as a form of clarifying the contents again propaganda. In addition, flabby communi-cation with dialect or local language style makes the speech partner more deeply the contents of his da'wah.